2019
DOI: 10.1155/2019/1028672
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting of Urinary Sodium and Potassium among Indonesian Schoolchildren Aged 9–12 Years: The Contribution of School Food

Abstract: Background. Sodium (Na) and potassium (K), the essential nutrients, have vital role in promoting cellular growth including growth and development of children. Excessive Na intake and inadequate K consumption, which consequently increases the risk of cardiovascular disease, have been reported. Spot electrolyte urine was highly correlated and validated with gold standard to estimate electrolyte dietary intake. This study aimed at predicting sodium and potassium intake using morning spot urine among Indonesian sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…In school-age children, Na intake exceeded the WHO recommendation, while K intake was below the recommended level; the Na-K ratio was 1.4 (95%CI: 1.1, 1.7). These results coincide with those obtained in Indonesian children between 9 and 12 years, who had a high Na intake (>2300 mg/day) and a low K intake (<2500 mg/day) [55]. On the other hand, in Spanish children between 9 and 13 years old, Na intake was close to 2500 mg/day, while K intake was 2800 mg/day [56].…”
Section: Discussionsupporting
confidence: 88%
“…In school-age children, Na intake exceeded the WHO recommendation, while K intake was below the recommended level; the Na-K ratio was 1.4 (95%CI: 1.1, 1.7). These results coincide with those obtained in Indonesian children between 9 and 12 years, who had a high Na intake (>2300 mg/day) and a low K intake (<2500 mg/day) [55]. On the other hand, in Spanish children between 9 and 13 years old, Na intake was close to 2500 mg/day, while K intake was 2800 mg/day [56].…”
Section: Discussionsupporting
confidence: 88%
“…In schoolchildren, Na consumption exceeds the WHO recommendation, while K consumption was below the recommended level; the Na / K ratio was 1.4 (95% CI 1.1, 1.7). These results coincide with those obtained in Indonesian children between 9 and 12 years, who had a high Na consumption (>2 300 mg / day) and a low K consumption (<2 mg/day) [55]. On the other hand, in Spanish children between 9 and 13 years old, Na consumption was close to 2 500 mg/day, while K consumption was 2 800 mg/day [56].…”
Section: Discussionsupporting
confidence: 88%
“…The elements Na, Ca, Mg, K, S, P, and B are metals indispensable for the correct functioning of all physiological systems in the human body [74][75][76][77][78][79]. Their presence in the diet in excess or deficient quantities can lead to chronic diseases [80][81][82][83]. In the present study, most honey samples were found to have intermediate HCR levels of Mg and Ca, with only a small number demonstrating higher values.…”
Section: The Assessment Of Mms Concentration In Honey Samples From Nw and Central Poland And Other Eu Countriesmentioning
confidence: 52%